Radio 2.0 in higher education communities - Piñeiro, Teresa
The web 2.0 raises new challenges and opportunities in many different fields of activity, namely because it introduces different approaches and possibilities to the relationship among participants both at institutional and individual levels. On the Higher Education context many changes are occurring due to the introduction of new learning paradigms, many of them take advantage of web 2.0 technologies to configure more effective and diverse scenarios to support the work of students and teaching staff. Social networks are currently being adopted in many Higher Education communities as platforms to support the interaction among community members, taking advantage of the potential of those networks to foster strong and meaningful relationships and support the awareness and consolidation of group identity. This potential is being explored to promote new possibilities for teaching and learning that include new approaches such as the personal learning environments. This article addresses the potential that radio services have for Higher Education communities in a web 2.0 world focusing on the case of the Universty of Aveiro (Portugal). The article explores the potential of articulation between radio and the social web focusing on the entertainment, the support to teaching and learning and the institutional communication points of view.